Perhitungan Tarif Kamar Hotel Surya Raya Menggunakan Activity Based Costing - Lukman, Rica; Afag, Laila Richa Rachmawati (STIE Amkop Makassar, Indonesia, 2025)
The room occupancy rate at the Surya Raya Hotel tends to fluctuate from July 2024 to June 2025. This problem requires hotel business owners to be truly wise in determining room rates. This community service program aims to provide a deeper understanding to business owners, especially the Surya Raya Hotel, regarding the calculation of hotel room rates. The analytical method used is descriptive, where this method is used to describe and analyze the results of data obtained during community service and then draw conclusions. Data collection techniques use interviews, observation, and documentation. Based on the results of the calculation of tariff determination using the ABC method at the Surya Raya Hotel, it shows that there is a difference in profit from the rates offered to customers. Therefore, it can be concluded that the Surya Raya Hotel earns a profit from the rates offered to customers. The calculations that have been carried out by the Community Service Team can be a reference in determining the basic price of a hotel room based on the activities carried out by the Surya Raya Hotel.